THE INFLUENCE OF KNOWLEDGE ON SEX EDUCATION FOR CHILDREN AGED 3-5 YEARS USING THE STORYTELLING METHOD USING PUPPETS - Susilowati, Purwantini; Idhayanti, Ribkha Itha; Lusiana, Arum (Poltekkes Kemenkes Semarang, 2025)
Background: In 2021 the number of cases of violence against children in Magelang Regency, Central Java will increase compared to the previous year, especially cases of sexual harassment and violence. It is essential to give sexual education to children from an early age because sexual education knowledge is an effort to prevent unplanned negative impacts, preventing sexually transmitted diseases, depression, and feelings of guilt which have long-term consequences.Methods: This research aims to determine the effect of sex education knowledge on children aged 3-5 years using the storytelling method using puppets. This research was conducted at the Harapan Bunda Playgroup, Krinjing Village, Dukun District. This type of research uses a pre-experimental design with a one-group pretest post-test design. The population of this study was students aged 3-5 years in the Harapan Bunda Playgroup in May 2024, with a total of 40 respondents. The sampling technique is using total sampling (census). Data analysis used the Wilcoxon test. All research samples were given pre-test and post-test questionnaires.Results: The research results showed that there was an influence on knowledge of sex education for children aged 3-5 years using the storytelling method using puppet media with a p-value of 0.000 < Î± 0.05.Conclusion: With the results of this research, it is hoped that midwives will be able to provide information, especially to parents of children aged 3-5 years, about sex education by providing counseling using varied and interesting methods and media.